Dynamics of judo contests performed by finalists of European Championships (Rotterdam 2005) - Boguszewski, D.; Boguszewska, K. (Archives of Budo, 2006)
Study aim: To analyse struggle dynamics of the best European judoists (male and female). It was assumed that finalists of top-rank European tournaments demonstrated supreme skills. Material/methods: The analysis included 14 final contests, male and female (7 each) from European Championships in Rotterdam 2005. The following indices of struggle dynamics were determined: of offensive/ defensive activity (AI), of effective offensive actions (EA), of effective counterattacks (EC), of effective actions without counterattacks (ED), and global index of struggle dynamics (SDI). Results: The gold medallists exhibited a markedly higher struggle dynamics in mean EA, EC and SDI values than their opponents. Otherwise, no significant differences were noted between male and female athletes or between weight categories. Conclusions: Changes in the rules of judo contest should aim at increasing struggle dynamics. Besides, training of tactical skills should focus on fastest gaining a point advantage (by throw or holding, or by making the competitor break rules), as well as on effective defensive actions and on making use of opponent`s potential mistakes in the situation of own advantage.